2021
DOI: 10.26508/lsa.202101048
|View full text |Cite
|
Sign up to set email alerts
|

SnRNA sequencing defines signaling by RBC-derived extracellular vesicles in the murine heart

Abstract: Extracellular vesicles (EVs) mediate intercellular signaling by transferring their cargo to recipient cells, but the functional consequences of signaling are not fully appreciated. RBC-derived EVs are abundant in circulation and have been implicated in regulating immune responses. Here, we use a transgenic mouse model for fluorescence-based mapping of RBC-EV recipient cells to assess the role of this intercellular signaling mechanism in heart disease. Using fluorescent-based mapping, we detected an increase in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 79 publications
1
14
0
Order By: Relevance
“…68 Analysis of the miRNA cargo of human RBC-derived EVs identified miR-451a, miR-486, and miR-92a as highly enriched miRNAs. 63 miR-451a, miR-486, and miR-92a are also abundantly expressed in RBCs. 18 Another study revealed that miR-1246 and miR-150 were the most abundant miRNAs present in RBC-derived EVs during storage.…”
Section: Rbc-derived Mirnasmentioning
confidence: 99%
See 1 more Smart Citation
“…68 Analysis of the miRNA cargo of human RBC-derived EVs identified miR-451a, miR-486, and miR-92a as highly enriched miRNAs. 63 miR-451a, miR-486, and miR-92a are also abundantly expressed in RBCs. 18 Another study revealed that miR-1246 and miR-150 were the most abundant miRNAs present in RBC-derived EVs during storage.…”
Section: Rbc-derived Mirnasmentioning
confidence: 99%
“…Studies have also shown that a significant proportion of EVs found in peripheral blood is derived from RBCs, 23,61 and RBC-derived EVs interact with neighboring cells exerting biological effects. 26,62,63 Several studies highlight that RBC-derived EVs possess a crucial role in RBC communication with the myocardium and endothelium in order to regulate cardiovascular homeostasis, redox balance, immunomodulation, and coagulopathy. 26 There is an increase in RBC-EV-targeted cardiomyocytes in a mouse model of ischemic heart failure.…”
Section: Rbc-derived Mirnasmentioning
confidence: 99%
“…Although RBCs lack the signalling mechanism required for endocytosis or exocytosis, circadian‐driven complement (C5b‐9)‐mediated ectocytosis is believed to be the main mechanism for daily generation of RBC‐derived EVs in the blood circulation both under healthy and inflammatory states (Donadee et al., 2011 ; Iida et al., 1991 ; Karasu et al., 2018 ; Thangaraju et al., 2021 ). In collaboration with Dr. Das, the targets of circulating RBC‐EVs were recently identified using a cre‐loxp murine model (Valkov et al., 2021 ). RBCs isolated from an erythroid‐specific‐cre (EpoR‐cre) mice underwent complement activation, and the resulting EVs were purified and intravenously administered into Rosa26‐mTmG reporter mice.…”
Section: Lessons From Other Cell Membrane‐derived Vesicles and Other ...mentioning
confidence: 99%
“…As mentioned before, RBCEVs have been known as key regulators of various physiological and pathological processes, including coagulation, inflammation, and also atherosclerosis and thrombosis [ 173 ]. Moreover, there is strong evidence that the plasma concentrations of RBCEVs are elevated in the development of cardiovascular-related disease, which can further lead to vascular dysfunction [ 174 ]. Furthermore, RBCs infected by Plasmodium falciparum are able to transfer DNA (drug resistance and fluorescent protein genes, etc.)…”
Section: Rbc-derived Extracellular Vesicles (Rbcevs): Biogenesis and ...mentioning
confidence: 99%